Pengaruh Harga, Lokasi Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Bahan Material Bangunan UD. Jaya Abadi Di Sampang - Salman Firmansyah; Triana Setiyarini (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This study aims to empirically test price, location, and service quality on purchasing decisions for building materials at UD. Jaya Abadi in Sampang. Respondents in this study were consumers of UD. Jaya Abadi, who bought at least once. Sampling was selected using purposive sampling. The method of analysis used in this research is multiple linear regression. The results of this research hypothesis testing indicate that the price has an effect on purchasing decisions for building materials at UD. Jaya Abadi. Location affects the decision to purchase building materials at UD. Jaya Abadi. Service quality affects the decision to purchase building materials at UD. Jaya Abadi. Price, location, service quality simultaneously influence the purchasing decision for building materials at UD. Jaya Abadi.